INTEGRASI GENAI-AUTOMATIC CORRECTIVE FEEDBACK (ACF) DALAM MENULIS KOLABORATIF BERBASIS INSTRUKSI METAKOGNISI TERHADAP KEMAMPUAN MENULIS ESAI ARGUMENTATIF - Meliyawati Meliyawati; Tatu Munawaroh; Rizdki Elang Gumelar (Universitas Negeri Makassar, 2026)
The purpose of this study was to investigate the impact of GenAI-Automatic Corrective Feedback (ACF) integration in collaborative writing based on metacognitive instruction on argumentative essay writing ability. The method used in the study was a quasi-experimental method involving 220 students divided into two groups. The experimental group received GenAI-Automatic Corrective Feedback (ACF) integration intervention with collaborative writing based on metacognitive instruction, while the control group used a genre-based writing approach. The instruments used included writing assessments covering lexical, accuracy, and fluency. Data analysis used included descriptive analysis, ANOVA, and regression analysis. The findings of the study showed that the GenAI-ACF intervention in collaborative writing based on metacognitive instruction was able to improve argumentative essay writing ability more significantly than the genre-based writing intervention. Improvement in argumentative essay writing ability was seen in several aspects, including lexical complexity (lexical density, lexical sophistication, and lexical variety), accuracy, and fluency. The components of metacognitive instruction that contributed most significantly to argumentative essay writing ability were the evaluation and declarative knowledge components. Thus, it can be concluded that the integration of GenAI-ACF in collaborative writing based on metacognitive instruction significantly contributes to the quality of argumentative essays. This study implies that the integration of technology use and metacognitive instruction in collaborative writing can optimize writing competence.